An investigation of surface deformation over oilfield in Southwest Iran (2003–2010) using InSAR and physical modelling. Issue 14 (17th July 2020) - Fatholahi, Narges; Akhoondzadeh, Mehdi; Bahroudi, Abbas
ABSTRACT: Land subsidence is one of the most hazardous phenomena. Rapid rate subsidence corresponds to human activities such as subsurface withdrawal. Therefore, local changes in surface elevation and its associated response has the potential to damage the industrial structures. In this research, the small baseline subset (SBAS) algorithm is applied to perform an Interferometric Synthetic Aperture Radar (InSAR) time series analysis within 2003 and 2010 over a giant oilfield located in the Zagros fold-thrust belt in southwest of Iran. Thirty-one interferograms are generated using 18 Envisat ASAR images. The mean velocity map obtained in the Line-Of-Sight (LOS) direction of satellite to the ground reveals the maximum subsidence on order of 17.3 mm per year over the field due to both tectonic and non-tectonic features. In order to assess the effect of non-tectonic features such as petroleum exploitation on surface displacement, the results of InSAR have been compared with the oil production rate. Also, a physical model of reservoir pattern has been developed using 2D seismic profiles as the way to estimate tectonic deformation which indicates the influence of depth variations of the Gachsaran salt decollement on structural style.